Pengaruh Human Resource Development Practice terhadap Organizational Commitment karyawan PT. Ramayana Lestari Sentosa Tbk Cengkareng melalui variabel Employee Engagement dan Employee Turnover Intetions - Putra, Andreas Wahyu Gunawan; Nabilah, Eva; Klaudia, Stiven (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
A well-prepared abstract enables the reader to identify the basic content This study aims to examine the influence of human resource development practices, organizational commitment, and employee engagement on employee turnover intentions at PT Ramayana Lestari Sentosa Tbk Cengkareng. A quantitative approach was used, with survey data collected through questionnaires distributed to employees. The sample size ranged from 170 to 340 respondents. Data were analyzed using descriptive statistics and Structural Equation Modeling (SEM) with the AMOS software. The results showed that human resource development practices had a positive effect on employee engagement. However, organizational commitment did not significantly affect engagement. Surprisingly, employee engagement showed a positive influence on turnover intentions. On the other hand, human resource development practices negatively affected turnover intentions, indicating that good HR practices may reduce employees' desire to leave. Mediation tests revealed that employee engagement did not significantly mediate the relationships between variables. These findings suggest that while HR development practices can enhance engagement, they may not be sufficient to reduce turnover intentions